LIVING VALUE DALAM KEHIDUPAN PONDOK PESANTREN SALAF TARBIYATUN NASYI’IN PACULGOWANG - Iva inayatul ilahiyah; M. Nur Salim; Aida Arini (EL-Islam, 2020)
Education is an instrument in cultivating the value of tolerance. The focus of this research is Living value in the life of Pondok Pesantren Salaf Tarbiyatun Nasyi'in Paculgowang. This type of research uses a descriptive qualitative approach. Data collection from this study contains data quotations to provide an overview of the presentation of the report. Data comes from, field notes, interview manuscripts, photos, personal documents, etc. The results of the observations show that the planting of pesantren living values ​​is carried out in 3 stages, namely Aqidah, worship, and morals.